National culture and public-sector budgeting: the mediating role of country-level institutions using a structural equation modeling approach. Issue 3 (15th November 2021) - Zarei, Hamid; Yazdifar, Hassan; Dahmarde Ghaleno, Mohsen; Namazi, Navidreza
Abstract : Purpose: Despite cultural dimensions being included in hundreds of business and management research studies, there have been relatively few studies in public-sector accounting that include the use of cultural dimensions. It is posited that national cultural variables impact the institutions, which, in turn, have an influence on public-sector budgeting. The study aims to contribute to the literature by examining these relations in 31 countries. Design/methodology/approach: These relationships are empirically evaluated by structural equation modeling using measures of national culture from Global Leadership and Organizational Behavior Effectiveness (GLOBE) study and Worldwide Governance Indicators (WGIs) measures named institutions from the World Bank. Furthermore, measures of public-sector budgeting are evaluated in which public-sector budgeting is classified according to the legislative power of the purse and budget transparency. Findings: Generally, findings reveal that institutions mediate the relationship among national cultural variables and budgeting at the national level. By that means, budgeting in a given nation is linked to the nation's supporting institutions which, in turn, are influenced by the national culture of those who maintain them. Particularly, power distance and uncertainty avoidance impact budgeting through the full mediation of institutions. Research limitations/implications: The World Bank's database used for the institutions contained over 200 countries (Kaufmann et al., 2007); the GLOBE cultural database (House et al., 2004) contained data for 62 societies; the public-sector budgeting (Qi and Mensah, 2011) included power of the purse and budgeting transparency country scores for 49 countries and the datasets comprised 31 nations, mostly from Organisation for Economic Co-operation and Development (OECD) countries. While smaller than we would have preferred, the size is consistent with other international studies (for instance: Waldman et al., 2006; Kwok and Tadesse, 2006). Practical implications: The findings of the paper suggest that any plan to improve a nation's budgeting should consider the links between budgeting, supporting institutions and the culture of those that run them. The formal adoption of new methods and standards by supporting institutions may not be enough without accompanying efforts to transform national culture. Originality/value: The theoretical contribution of the paper is discussed further in the paper.